Identification of Chlamydia abortus and Chlamydia pecorum in water buffaloes (Bubalus bubalis) and cows cohabitating the same herd - Limón-González, Magdalena; Hernández-Castro, Rigoberto; Palomares Reséndiz, Gabriela; Herrera López, Enrique; Díaz Aparicio, Efrén (Buffalo Bulletin, 2023)
The aim of this study was to determine the presence of Chlamydia spp. in a dual-purpose zebu and water buffalo-mixed herd cohabitating in a ranch located in southern Mexico. The zootechnical purpose of this herd is milk and cheese production. A total of 52 vaginal exudate samples were obtained from clinically healthy water buffaloes, less than one month after parturition, and two vaginal exudate samples were taken from cows that had recently aborted. L929 cells were used for bacterial isolation. Two of these cultures were infected, confirmed by direct immunofluorescence. Total DNA was extracted for analysis with two types of real-time PCR, a Chlamydiaceae-specific real-time PCR and another species-specific real-time PCR for C. abortus, C. psittaci and C. pecorum. Two Chlamydia isolates were obtained, one from a water buffalo positive to C. abortus and C. pecorum, the other from a cow positive to C. abortus. This is the first report of the presence of C. abortus and C. pecorum in water buffaloes in Mexico. C. abortus was also detected in one cow living in the same herd as the water buffaloes.